Pengaruh Love Of Money, Machiavellian, Idealisme Dan Religiusitas Pada Persepsi Etis Mahasiswa Akuntansi Di Kota Padang - Rahmad Akbar; Indrayeni (CV. ITTC INDONESIA, 2024)
This study aims to determine the influence of love of money, Machiavellian, idealism, and religiosity on the ethical perception of accounting students in Padang City. The population in this study is Accounting Students in Padang City. The sample in this study used quota sampling method. Analysis technique using multiple linear regression analysis method The results of this study show love of money, Machiavellian, idealism, have no effect on the ethical perception of Accounting Students in Padang City. While religiosity has a significant positive effect on the ethical perception of accounting students. But simultaneously or together love of money, Machiavellian, idealism, and religiosity influence the ethical perceptions of accounting students. The contribution of this research is expected to provide accounting students with a better understanding of the influence of certain factors on their ethical behavior, so that they can make better and more responsible decisions in the future, providing valuable insight for readers, especially students, lecturers, accounting practitioners, and researchers, about what factors can influence students' ethical perceptions in local contexts, can gain a better understanding of how the drive to achieve financial success, manipulative attitudes, moral beliefs, and religiosity can influence students' ethical attitudes, and can be a basis for universities to develop curricula that are more effective in educating students about accounting ethics. By understanding the factors that influence students' ethical perceptions, universities can adapt learning approaches and offer more holistic training programs to help students develop a better understanding of ethics in accounting practice.